Optimization and Interpretation of Heat Distribution in Sterilization Room Using Convection Pipe - Abdurrahman, Abdurrahman; Umam, Rofiqul; Irzaman, Irzaman; Palupi, Endah Kinarya; Saregar, Antomi; Syazali, Muhamad; Junaidi, Rahmad; Wahyudianto, Benny; Adi, Langit Cahya (Universitas Pendidikan Indonesia, 2019)
In mushroom cultivation of white oyster mushroom (P. ostreatus), problems in the contamination during the production are typically found. This contamination is due to the issue in controlling temperature during the media sterilization for growing the fungus (bag-log). This suboptimal sterilization causes unwanted bacteria and spores to grow. To reduce the amount of contamination, the purpose of this study was to demonstrate and evaluate the temperature distribution using one convection pipe with diameter of 6 and 8 cm. The fuel used for this sterilization process is rice husk. Sterilization itself aims to kill other unwanted bacteria and spores on the bag-log. Sterilization was done by traditional steaming bag-log drums arranged in four rows upwards for 6 hours. Convection pipes were built in drums. The steamer was done by performing two retrievals of data. From the experiment results, the use of convection pipe of 8 cm was better than the convection pipe of 6 cm. This is shown from the amount of fungal contamination in convection pipes were less in 8. The result of temperature measurement using dual laser infrared thermometer was also completed and interpreted using Matrix Laboratory with interpolation method to get heat distribution result.